Hydrogeology of three hard rock catchments in Britain - Mazadu Dader Bako (1988)
The ground water regimes of three small, undisturbed (natural) and accessible hard rock catchments representing the South, Midlands and the North of Great Britain have been hydrogeologically investigated and compared. There is a dearth of hydro geological information on hard rock areas in Britain. This is because the general availability of surface water and extensive sedimentary aquifers has not encouraged ground water prospecting in hard rock areas. In view of this, low flow study was considered essential since geology exerts a great influence on its characteristics. This was carried out using baseflow recession analysis. From a combination of practical, empirical and theoretical considerations aided by statistical analysis on a computer, baseflow recession constants which dynamically reflect the physiographic and geologic controls within a catchment were derived for the catchments investigated. These were used to characterise the behaviour of the low flows. A new method which is free of random selection of data for baseflow recession analysis is presented and a model for the curve fitting both by computer and manual methods are fully discussed and its application is also presented. Water balance computations for each of the three catchments is presented in chapter 2. Lithological units were identified by a detailed geological study. These were further investigated using resistivity and electromagnetic methods of geophysical survey. Hydrogeological properties of the aquifers were investigated by pumping test analysis and subsequent comparison of hydraulic conductivities from soils and baseflow studies. A water chemistry investigation of spring, river and rain waters has been carried out to try and defme flow paths of the ground water and this is presented in chapter 7. From these investigations, this research concludes that large community water supplies through boreholes can be economical only in one of the catchments (East Dart catchment). In the other two catchments (Blackbrook and Calder catchments), small community and household supplies are possible through boreholes (in some areas) and large diameter wells.